2018
DOI: 10.1021/acs.estlett.8b00122
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Defluorination of Branched Per- and Polyfluoroalkyl Substances with Cobalt Complex Catalysts

Abstract: This study investigates structure−reactivity relationships within branched per-and polyfluoroalkyl substances (PFASs) undergoing cobalt-catalyzed reductive defluorination reactions. Experimental results and theoretical calculations reveal correlations among the extent of PFAS defluorination, the local C−F bonding environment, and calculated bond dissociation energies (BDEs). In general, BDEs increase in the following order: tertiary C−F bonds < secondary C−F bonds < primary C−F bonds. A tertiary C−F bond adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 47 publications
4
87
0
Order By: Relevance
“…This facile dissociation of secondary C-F bonds is due to their lower bond dissociation energy compared to the primary C-F bonds, as noted in a few earlier studies. 23,24 Contrary to the addition of a single electron, we find that the spin-density can evolve in two different ways with the addition of multiple electrons, as shown in the middle and bottom panels of figure 3. We refer to these different regimes as a trans-type (middle panel) or cis-type elimination (bottom panel) based on how the fluorine atoms have dissociated from the PFAS backbone structure.…”
Section: Pccp Communicationmentioning
confidence: 83%
See 1 more Smart Citation
“…This facile dissociation of secondary C-F bonds is due to their lower bond dissociation energy compared to the primary C-F bonds, as noted in a few earlier studies. 23,24 Contrary to the addition of a single electron, we find that the spin-density can evolve in two different ways with the addition of multiple electrons, as shown in the middle and bottom panels of figure 3. We refer to these different regimes as a trans-type (middle panel) or cis-type elimination (bottom panel) based on how the fluorine atoms have dissociated from the PFAS backbone structure.…”
Section: Pccp Communicationmentioning
confidence: 83%
“…For example, Liu et al have shown that fluorine atoms attached to a C=C bond (i.e., sp 2 carbon atoms) dissociate more readily compared to fluorine atoms attached to a C-C bond (sp 3 carbon atoms). 23 Since most of our simulations with excess electrons resulted in a trans-type elimination with the formation of a C=C bond (which is known to be more susceptible to defluorination), we infer that this trans-type intermediate plays a crucial role in PFAS defluorination, which could explain the PFAS degradation (with excess electrons) observed by Su et al 20 Apart from the trans-type intermediate, we also found that an HF molecule was formed during our simulations (see figure S5 and the Supplementary Information for further details).…”
Section: Pccp Communicationmentioning
confidence: 99%
“…where H* represents the enthalpy of formation. 8 DNA Extraction and Quantitative Polymerase Chain Reaction. Biomass from 0.5 mL of the culture was sampled from each biological replicate.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Reductive defluorination of long-chain perfluorinated compounds can be catalysed by natural and anthropogenic compounds containing cobalt. 190 This study did not report defluorination of TFA but the conditions for these reactions are unlikely to be found in the environment.…”
Section: Insert Fig 11 After This Pointmentioning
confidence: 91%